Conocimientos y prácticas sobre prevención y manejo de enfermedad diarreica aguda, en madres de niños/as del Centro Infantil del Buen Vivir Yahuarcuna MIES, Loja 2014-2015 - Lima Castillo, Verónica Elizabeth (2015)
The Illness Diarreica Aguda is the second biggest cause of death in children younger than five years, it is an illness that it is possible to prepare by means of the access to the drinking water and to suitable services of sanitation and hygiene. The present investigation tried: to determine the knowledge and the maternal practices on prevention and handling of Illness Diarreica Aguda. It was a study of descriptive type, the universe was constituted by 98 mothers of children / experts who are present at the CIVB. The skill that was used for the information compilation was the survey, and as he arranged the questionnaire. The results show that as for the knowledge of the mothers the majority defines correctly the diarrhea, likewise the factors to develop it, the measurements that diminish the danger of producing it, the symptoms to take the child / girl of an urgent way to the health service or hospital, preparation of the salt of oral rehydration and home-made oral whey as well as also the signs of dehydration and signs of signs of alarm to prepare complications. As for the practices a significant group of mothers realize practices adapted on: complementary feeding from six months of age, measurements for the consumption of sure water, elimination of served and black waters, cleanliness of the feeding-bottle, exclusive breast feeding up to six months, washed of hand, care of the food before to its ingestion and preparation, type of liquid and time that passes to offer it, breast feeding and daily feeding during the process diarreico. While they have inadequate practices as for the presence of animals intradomiciliarios since they indicate to have animals inside its hearth. Key words Illness Diarreica Aguda, Knowledge, You Practise, Prevention.